Hubungan Punishment Dan Kedisiplinan Dengan Kinerja Perawat - Febriani, Resty; Solehudin, Solehudin; Lannasari, Lannasari (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
In increasing optimal employee work productivity, with punishment, this research highlights the relationship between punishment and discipline with the performance of nurses in hospitals. Dr. Hafiz Cianjur. This research is very important to carry out in order to improve nurse discipline. With this research, it is hoped that there will be increased discipline for nurses and excellent service to the community can be maximized so that trust will arise from the community itself. The aim of this research is to determine the relationship between punishment and discipline with the performance of nurses in hospitals. Dr. Hafiz Cianjur. This study uses a quantitative approach. The research method used is descriptive correlation. The sample population was 214 nurses with a total sample size of 139 nurses taken using the probability sampling method. Data collection is in the form of a questionnaire. This research analysis uses univariate to describe the frequency distribution and Pearson test. The research results show that there is a relationship between punishment and discipline and the performance of nurses in hospitals. Dr. Hafiz Cianjur (p=0.001). Nurses are expected to improve performance and discipline to prevent punishment.